PENERAPAN EDUKASI PHBS BAGI SISWA SEKOLAH DASAR MELALUI PENDEKATAN KEPERAWATAN KOMUNITAS UNTUK MEMBANGUN GENERASI SEHAT - Fadhilah, Miftah Kamilia; Kasih, Raisha Aulia; Septiyanti; Wijaya, Andra Saferi (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2025)
Implementation of Clean and Healthy Living Behavior (PHBS) from an early age is a strategic step in improving children's health and preventing various diseases. This study aims to improve the knowledge and skills of students of Elementary School 19 Bengkulu City through PHBS education activities focused on the practice of washing hands with soap and brushing teeth properly. The activity was carried out on April 16, 2025 with a quasi-experimental approach using a one group pre-test and post-test design. Education was delivered through leaflets, posters, videos, and direct demonstrations by students. Evaluation was carried out using a questionnaire instrument before and after counseling. The results showed a significant increase in the level of student knowledge after participating in the activity, from 72% in the poor category to 62% in the good category. This activity is effective in shaping student awareness and behavior regarding the importance of maintaining personal hygiene, and can be used as a model for ongoing education in other elementary schools to form a healthy and independent generation.